PENGARUH HUBUNGAN ATASAN BAWAHAN, DISIPLIN KERJA DAN PENGEMBANGAN KARIR TERHADAP KINERJA PEGAWAI PADA KANTOR KECAMATAN WENGGEDUKU KABUPATEN KONAWE - Kamara, Oom; Abbas, Bakhtiar; Putera, Asrip (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2024)
This study aims to determine and analyze the influence of superior-subordinate relationship, work discipline, and career development on employee performance at the Wenggeduku Subdistrict Office, Konawe Regency. The sample in this study consisted of all employees at the Wenggeduku Subdistrict Office, Konawe Regency, totaling 31 individuals. This study uses multiple linear regression analysis. The results of the study show that: (1) Superior-subordinate relationship, work discipline, and career development have a positive and significant effect on employee performance. This means that improving the superior-subordinate relationship, work discipline, and career development will enhance employee performance at the Wenggeduku Subdistrict Office, Konawe Regency. (2) Superior-subordinate relationship has a positive and significant effect on employee performance. (3) Work discipline has a positive and significant effect on employee performance. (4) Career development has a positive and significant effect on employee performance.